Research trends and hotspots of post-stroke cognitive impairment: a bibliometric analysis - Chi, Xiansu; Fan, Xueming; Fu, Guojing; Liu, Yue; Zhang, Yunling; Shen, Wei (Frontiers in Pharmacology, 2023)
Background: Post-stroke cognitive impairment (PSCI), is a major complication of stroke that affects more than one-third of stroke survivors, threatening their quality of life and increasing the risk of disability and death. Although various studies have described the etiology, epidemiology, and risk factors of PSCI, there is a limited number of comprehensive and accurate reports on research trends and hotspots in this field. Therefore, this review aimed to evaluate research trends, hotspots, and frontiers in PSCI using bibliometric analysis. Methods: We screened literature spanning 20 years in the Web of Science Core Collection: Science Citation Index Expanded (SCI-Expanded) database from January 1, 2003, to December 31, 2022. We included all eligible literature based on our comprehensive search strategy, inclusion criteria, and exclusion criteria. The analysis of annual publications, countries/regions, institutions, journals, co-cited references, and keywords were conducted using CiteSpace and VOSviewer, and the hotspots and major findings of PSCI were summarized. Results: A total of 1,024 publications were included in this review. We found that the number of publications on PSCI increased annually. These publications were published in 75 countries or regions by over 400 institutions. While Chinese institutions had the highest number of publications, their international influence was limited. The United States showed a strong influence in the field. The journal Stroke published the most publications (57) with a high impact factor and was considered the most co-cited journal. The most frequently cited references focused on the prevalence, incidence, neuropsychological assessment scales, criteria, and guidelines of PSCI. The strongest citation burst keywords for PSCI were "neurotrophic factor" and "synaptic plasticity", which were regarded as research focuses and research hotspots. Conclusions: This review provided a comprehensive summary of the literature of PSCI, identified the authoritative and frequently cited literature and journals, clarified the trends in PSCI research, and highlighted the hotspots in this field. Currently, studies on the mechanisms and treatment of PSCI are limited, and we hope that this review has effectively highlighted the research trajectory of PSCI and will lay the foundation for more innovative research in the future.